Impact of Facebook Marketing on Apparel Purchase Intention of Generation Z in Nepal - Saud, Hari Singh; Kumar, Rajender; Chataut, Ram Kumar (Far Western Review, 2025)
The study explores impact of Facebook marketing affects the purchase intentions of Generation Z apparel consumers in Nepal. The behaviors and habits of Generation Z, which are online, make it an ideal target of social media marketing. The research design employed in this study was a quantitative, cross-sectional research design. The survey was based on a simple online questionnaire involving the respondents of 399 respondents belonging to Generation Z in Nepal, and the results were analyzed using SmartPLS 4 software and partial least squares structural equation modeling (PLS-SEM). The results of the hypothesis established that the three predictors of the study, Facebook advertisement (Path Coefficient 0.332, p = 0.000), Facebook comments and recommendations (Path Coefficient 0.337, p = 0.000), and Facebook offers (Path Coefficient 0.192, p = 0.001) had statistically significant effects on purchase intention among the Gen Z consumers in Nepal. The findings depict that Facebook marketing affects brand awareness, brand engagement, and purchase intention. These results underscore the essential need to engage in informative social media marketing.